MUTU PELAYANAN KESEHATAN TERHADAP KEPUASAN PASIEN DI PUSAT KESEHATAN ANGKATAN DARAT (PUSKESAD) POLKES KABUPATEN TAKALAR - Andi Alim Bagu; Yuliana Baharuddin; Ali Imran (Politeknik Kesehatan Kemenkes Mamuju, 2017)
The quality of health services is one of main focus for community. Awareness of the quality of health services is increasing with the demand for improving the quality from service providers and community as a service user. The quality of health services greatly affects patient satisfaction. The design of this study is analytic survey research with cross sectional approach. The purpose of this study is to know the relation of quality of health service to patient satisfaction at Army Health Center (PUSKESAD) POLKES of Takalar Regency in 2017. The research is conducted at Army Health Center (PUSKESAD) POLKES Takalar District. The sample in this study are patients who treated at the Army Health Center (PUSKESAD) POLKES Takalar District in June of 2017 as many as 94 people using a simple random sampling technique. Data analysis in this research is univariate and bivariate analysis using chi square test. The results showed that there was a significant correlation between health service quality based on indicator physical appearance, reliability, responsiveness, assurance, and empathy with patient satisfaction with each p value = 0,000. It is hoped that the Army Health Center (PUSKESAD) POLKES can improve the quality of health services and the confidence of patients in utilizing health services more increase.